Reviewing adjustment dynamics in EMU : from overheating to overcooling - Deroose, Servaas; Langedijk, Sven.; Roger, Werner; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2004)
This paper analyses how adjustment dynamics, in an environment with some degree of price and wage rigidity, may create and strengthen asymmetric developments in a monetary union. It presents a simple illustrative model of adjustment dynamics that reproduces quite nicely actual developments in the first years of EMU. The model is used to analyse adjustments to two types of shocks • relative competitiveness shifts and • demand disturbances. It is shown that the interaction between real exchange rate adjustment and real interest rate developments may contribute to periods of overheating and overcooling during which output might be for a number of years either above or below potential. Furthermore, the paper looks at the circumstances in which smooth adjustment to shocks can be expected and, on the other hand, when a cycle with greater amplitude is more likely. Finally, the paper examines policy options that could improve the functioning of EMU. The analysis provides another strong argument for pressing ahead with reforms that increase flexibility in labour and product markets and further integrate the economies of the euro area.
Economic Papers